1980
DOI: 10.1121/1.385117
|View full text |Cite
|
Sign up to set email alerts
|

Dichotic CV recognition at various interaural temporal onset asynchronies: Effect of age

Abstract: Dichotic CV recognition at interaural temporal onset asynchronies (lag times) of 0, 30, 60, and 90 ms was investigated in normal hearing young and elderly subjects. The results for the young group were consistent with those reported in previous studies (Studdert-Kennedy et al., 1970; Berlin et al., 1973a). The older group demonstrated a mean right ear advantage (REA) at simultaneity of 12.7%, which was not significantly different from that of the young group (12.4%). This suggests that the processes subserving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0
3

Year Published

1984
1984
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 14 publications
2
13
0
3
Order By: Relevance
“…The presence of a signifi cant difference in HINT scores between N90 and N270, with better scores when the noise came from the left speaker in each group, is consistent with the previous fi ndings that aging causes progressive decline in the central processing of speech, and that this decline is greater for the left ear (right hemisphere) than the right ear (left hemisphere) input [Gelfand et al, 1980;Jerger et al, 1994;Alden et al, 1997;Greenwald and Jerger, 2001]. …”
Section: Hearing In Noise Testsupporting
confidence: 76%
“…The presence of a signifi cant difference in HINT scores between N90 and N270, with better scores when the noise came from the left speaker in each group, is consistent with the previous fi ndings that aging causes progressive decline in the central processing of speech, and that this decline is greater for the left ear (right hemisphere) than the right ear (left hemisphere) input [Gelfand et al, 1980;Jerger et al, 1994;Alden et al, 1997;Greenwald and Jerger, 2001]. …”
Section: Hearing In Noise Testsupporting
confidence: 76%
“…In particular, perception of left-ear targets of dichotic sentences deteriorates with age relative to perception of right-ear targets (Jerger, Stach, Johnson, Loiselle & Jerger, 1990, Jerger & Jordan, 1992, even in individuals with little or no change in their hearing sensitivity over a period of several years (Stach, Jerger & Fleming, 1985). In contrast, the right-ear advantage for brief, dichotically presented nonsense syllables, digits, or spondees does not appear to change (Gelfand, Hoffman, Waltzman & Piper, 1980, Martini, Bovo, Agnoletto, Da Col, Drusian, Liddeo & Morra, 1988. These reports suggest that a right-ear advantage increases both for peripheral hearing sensitivity and for speech tasks that rely on centrally mediated processes.…”
Section: Iintroductionmentioning
confidence: 50%
“…Also, an age-related increase of ear asymmetry has been reported: performance of the LE has been found to decrease stronger than performance of the RE (Jerger, Alford, Lew, Rivera, & Chmiel, 1995;Jerger, Chmiel, Allen, & Wilson, 1994;Strouse et al, 2000a;Strouse, Wilson, & Brush, 2000b). However, this finding is still controversial since some aging studies have failed to find such an effect (Gelfand et al, 1980;Martini et al, 1988) or found that age effects could only be perceived in focussed attention conditions, in particular when attention had to be focussed at the LE (Alden et al, 1997;Bouma & Van der Endt, 1993;Hallgren et al, 2001). Findings of decreased LE performance in elderly suggest that aging differentially affects functional hemispheric asymmetry.…”
mentioning
confidence: 89%
“…Indeed, research has demonstrated that the DLT performance of elderly is decreased compared to younger participants (Alden, Harrison, Snyder, & Everhart, 1997;Bouma & Van der Endt, 1993;Gelfand, Hoffman, Waltzman, & Piper, 1980;Hallgren, Larsby, Lyxell, & Arlinger, 2001;Martin & Cranford, 1991;Strouse, Wilson, & Brush, 2000a). Also, an age-related increase of ear asymmetry has been reported: performance of the LE has been found to decrease stronger than performance of the RE (Jerger, Alford, Lew, Rivera, & Chmiel, 1995;Jerger, Chmiel, Allen, & Wilson, 1994;Strouse et al, 2000a;Strouse, Wilson, & Brush, 2000b).…”
mentioning
confidence: 99%